2023
DOI: 10.3389/fphar.2023.1185418
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel copper metabolism-related risk model to predict prognosis and tumor microenvironment of patients with stomach adenocarcinoma

Abstract: Background: Stomach adenocarcinoma (STAD) is the fourth highest cause of cancer mortality worldwide. Alterations in copper metabolism are closely linked to cancer genesis and progression. We aim to identify the prognostic value of copper metabolism-related genes (CMRGs) in STAD and the characteristic of the tumor immune microenvironment (TIME) of the CMRG risk model.Methods: CMRGs were investigated in the STAD cohort from The Cancer Genome Atlas (TCGA) database. Then, the hub CMRGs were screened out with LASSO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…[8][9][10] As the development of next-generation sequencing technology, microarrays combined with bioinformatics analysis have been used widely to identify potential biomarkers for various complex diseases, which has provided new strategies for biomedical research. [11][12][13] Meanwhile, using bioinformatics research, Rivera C et al discovered that CXCL12 and its receptor gene CXCR4 were expected to monitor OLP occurrence and could be new therapeutic targets. [14] Other studies have shown that OLP patients had significantly elevated expression of NRIP1 (also known as RIP140), whose upregulation promoted the development of inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] As the development of next-generation sequencing technology, microarrays combined with bioinformatics analysis have been used widely to identify potential biomarkers for various complex diseases, which has provided new strategies for biomedical research. [11][12][13] Meanwhile, using bioinformatics research, Rivera C et al discovered that CXCL12 and its receptor gene CXCR4 were expected to monitor OLP occurrence and could be new therapeutic targets. [14] Other studies have shown that OLP patients had significantly elevated expression of NRIP1 (also known as RIP140), whose upregulation promoted the development of inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%